Porous structured titania by chemical methods - Ma, Bing (2008)
This thesis describes the synthesis and characterization of various porous titania structures, with specific emphasis on surface area and crystallinity. Materials having pore diameters ranging from ~2 nm to ~250 nm were prepared from hard anodic aluminium oxide templates (AAO) and soft block copolymer templates. The photocatalytic performance of these titanias was also evaluated.